Fathers Are Parents, Too! Widening the Lens on Parenting for Children's Development. (8th January 2018) - Cabrera, Natasha J.; Volling, Brenda L.; Barr, Rachel
Abstract: Why do fathers matter? Recent conceptual and theoretical advances regarding father–child relationships have demonstrated that fathers affect children's outcomes both directly and indirectly. To attain a complete developmental account of the ecologically rich contexts of child development, in this article, we recommend best practices regarding the conceptualization and assessment of father–child relationships that reflect contemporary family life. We also discuss conceptual and measurement issues pertaining to father–child relationships in different family configurations, including those with resident and nonresident fathers. We conclude with recommendations that can help developmental researchers advance our understanding of fathering, parenting, and children's development.